Development of Science Learning Device Oriented Guided Inquiry with Virtual Laboratory to Train Science Process Skills of Junior High School Students in Kendari - I Gede Purwana Edi Saputra; Harnipa Harnipa; Mariani Akhfar (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2021)
This research was based on the mismatch between the expectation of learning and the study result of IPA on Junior High School. That is why it needs efforts to improve the quality of the teaching and learning process by developing the learning instruments, which are eligible with the mean of IPA and the Graduation Competency Standard on Junior High School. The research purposed to describe the eligibility and effectiveness of the learning instrument of IPA on Junior High School, which is developed in the oriented inquiry by the virtual laboratory to practice the student's science process skills. The research is the development research that adapts the Kemp model. The development of learning instruments such as lesson plans, student worksheets, and assessment sheets. The research subject is the students of class 7 and 8, IX grade on Junior High School 5 Kendari. The implementation planning in-class uses one group pretest and post-test design and data analyzed descriptively. The research results are the learning instruments are eligible to be used, suitable student worksheets, and the student's handbook shows that the content and appearance are interesting. The lesson plan did well, and the majority of students' activity is how to solve a problem. The completeness of the results of the study are well done. Character attitude and social interactive are good. Students' response fir the learning is positive. The summarize of IPA, which is developed, is effective in practicing the science process skills for Junior High School students.